The Transforming Matrilineal Land Inheritance Practice - Jenesta Urassa (International Journal of Global Community, 2026)
The study examines the transformation of matrilineal land inheritance practice and women’s land rights in the context of intermarriage among the Luguru ethnic group. Data were collected through document review, interviews, and Focus Group Discussions (FGDs). The result identified several cases of intermarriage between matrilineal and patrilineal groups. Women married to men from other ethnic groups lose their rights to inherit land from their natal families. Marriages are increasingly becoming patriarchal, and men have changed their practices of moving to their wives’ households and passing land to their sisters’ children. However, the study also noted other barriers to women’s rights, such as increased land sales. Addressing women’s access to land requires policy frameworks that promote cultural practices of both matrilineal and patrilineal groups to reduce the impact of intermarriages on women’s rights. Policies should monitor and regulate land sales, which disadvantage weaker groups, especially women.